Lessons From EU-Projects for Energy Renovation - Van der Schoor, Tineke (Urban planning, 2022)
There is an urgent need for energy renovation of the existing building stock, in order to reach the climate goals, set in Paris in 2016. To reach climate targets, it is important to considerably lower energy demand as well as switch to fossil-free heating systems. Unfortunately, renovation rates across the EU remain at a low level of 1% per year. Deep renovation, which lowers energy use with 60% or more, accounts only for 0,2% of renovations. The heating transition thus progresses much more slowly than the electricity transition. We draw on the framework of technological innovation systems, which allows comparison of different transitions. In the literature, it is argued that the configurational nature of the renovation system is one of the main reasons for the slow heating transition. The renovation system is context-bound and consists of many actors both on the demand-side and the supply-side, which leads to a fragmented market. For increasing the speed of the heating transition, it is deemed important to counter this fragmentation. We carried out a review of reports and publications of EU-funded projects on energy renovation. In many projects fragmentation in the building sector was identified as one of the main obstacles. We analyzed the deliverables of these energy renovation projects to find tried and tested solutions. One of these is the so-called one-stop-shop, which promises to improve the organization of the supply side, while also providing an appropriate and affordable solution to the customer. In the discussion we argue that the energy renovation system could be improved by increasing collaboration on the supply side and at the same time simplifying the renovation process for customers. A promising tool to make this happen is the one-stop-shop.